Cylindrical battery and preparation method thereof
By regulating the parameter relationship between the diaphragm and the pole plate in a cylindrical lithium-ion battery, the interface stress release and gas emission are optimized, and the performance degradation and white spots caused by the pole plate expansion are solved, and the cycle life of the battery is improved.
Patent Information
- Application Number
- CN202411817475.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-28
AI Technical Summary
The deformation caused by the expansion of the electrode plate during charging and discharging of the cylindrical lithium-ion battery cannot be effectively released, resulting in a decline in battery performance and may cause uneven lithium-integrated white spots on the interface, affecting the battery service life.
By sequentially setting the negative electrode sheet, the B-side separator, the positive electrode sheet and the A-side separator, the A-side separator is a base film, and the B-side separator includes a base film and a coating layer, adjusting the specific relationship of each parameter to optimize the emission of interface stress release and gas-generated gas.
The interface stress release and emission of gas-generated gases of winding cylindrical batteries are effectively optimized, the cycle life of the battery is improved, and the appearance of white spots is reduced.
Smart Images

Figure CN119542564A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a cylindrical battery and a preparation method thereof. Background Art
[0002] At present, lithium-ion batteries have been widely used, but with the improvement of people's material needs, the demand for long-cycle batteries is getting higher and higher. Among them, cylindrical batteries, as the earliest commercialized lithium-ion batteries, have always been favored by the market. As we all know, during the charging and discharging process of lithium-ion batteries, the volume of lithium-ion batteries will be deformed due to the release and embedding of lithium ions in the positive and negative electrodes. Due to the unique spiral winding structure of cylindrical batteries, the deformation caused by the expansion of the pole pieces during the charging and discharging process of cylindrical batteries cannot be effectively released, which will cause the performance of cylindrical batteries to decline. It is more obvious during the first charging and discharging process. If the design is unreasonable, the battery interface will be tightly fitted between the positive and negative pole pieces and the diaphragm, and the gas generated during the formation cannot be discharged in time, resulting in the formation of white spots with uneven lithium embedding on the interface, thereby affecting the later service life of the battery.
[0003] Therefore, there is an urgent need to improve the battery interface and optimize the interface stress release and gas emission of the wound cylindrical battery, thereby improving the cycle life of the battery.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a cylindrical battery and a preparation method thereof, aiming to optimize the interfacial stress release and the emission of gas produced by formation of a wound cylindrical battery, thereby improving the cycle life of the battery.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a cylindrical battery, which is formed by winding a negative electrode sheet, a B-side separator, a positive electrode sheet and an A-side separator arranged in sequence;
[0008] The A-side diaphragm is a base film, and the B-side diaphragm includes a base film and a coating layer coated on the base film;
[0009] The parameters of the A-side separator, B-side separator and negative electrode sheet satisfy the following relationship:
[0010] h3=k1×ha×ρ / 2, where k1=0.9-1.1;
[0011] σb=k2×σa×(1-λ)×(1-Ψ), where k2 is 1.3-1.6;
[0012] h2+h3=h1×k3, the value of k3 is 90%-110%;
[0013] Where, h1 represents the thickness of the A-side diaphragm, in μm;
[0014] h2 represents the thickness of the base film of the B-side diaphragm, in μm;
[0015] h3 represents the thickness of the coating layer, in μm;
[0016] ha represents the thickness of the negative electrode at 0% SOC, in μm;
[0017] ρ represents the full-charge expansion rate of the negative electrode, in %;
[0018] σb represents the porosity of the base film of the B-side diaphragm, in %;
[0019] σa represents the porosity of the A-side diaphragm, in %;
[0020] λ represents the ratio of the coating area of the coating layer to the base film area, in %;
[0021] ψ represents the swelling of the coating layer, in %.
[0022] In an optional embodiment, the material of the A-side diaphragm is polyethylene.
[0023] In an optional embodiment, the porosity σa of the A-side diaphragm is 30%-60%;
[0024] And / or, the thickness h1 of the A-side separator is 5 μm-30 μm.
[0025] In an optional embodiment, the base film of the B-side diaphragm is made of polypropylene;
[0026] and / or, the porosity σb of the base film is in the range of 30%-60%, and the thickness h2 is in the range of 6 μm-30 μm;
[0027] And / or, the material of the coating layer is selected from at least one of polyvinylidene fluoride, epoxy resin, polyurethane, acrylate and silane.
[0028] In an optional embodiment, the swelling ψ of the coating layer is 2%-10%;
[0029] and / or, the ratio λ of the coating area of the coating layer to the base film area is 10%-40%;
[0030] And / or, the coating layer is formed by a dot coating process and is coated on one side of the base film.
[0031] In an optional embodiment, the full charge expansion rate ρ of the negative electrode sheet is 0%-30%;
[0032] And / or, the thickness ha of the negative electrode active layer of the negative electrode sheet in the 0% SOC state is 50 μm-200 μm.
[0033] In an optional embodiment, it is defined that both the positive electrode sheet and the negative electrode sheet have an A surface and a B surface, wherein the A surface is the surface close to the center of the circle, and the B surface is the surface away from the center of the circle;
[0034] The winding order is that the A-side separator faces the A-side of the negative electrode sheet and the B-side of the positive electrode sheet; the B-side separator with the coating layer faces the B-side of the negative electrode sheet, and the other side faces the A-side of the positive electrode sheet.
[0035] In an optional embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active coating attached to both sides of the negative electrode current collector, and the active material in the negative electrode active coating is selected from at least one of graphite, silicon-based negative electrode and lithium titanate;
[0036] And / or, the positive electrode sheet includes a positive electrode current collector and a positive electrode active coating attached to both sides of the positive electrode current collector, and the active material in the positive electrode active coating is selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide and lithium iron phosphate.
[0037] In a second aspect, the present invention provides a method for preparing a cylindrical battery according to any one of the aforementioned embodiments, comprising: when providing an A-side separator, a B-side separator and a negative electrode sheet, making each parameter satisfy the following relationship:
[0038] h3=k1×ha×ρ / 2, where k1=0.9-1.1;
[0039] σb=k2×σa×(1-λ)×(1-Ψ), where k2 is 1.3-1.6;
[0040] h2+h3=h1×k3, the value of k3 is 90%-110%;
[0041] The negative electrode sheet, B-side separator, positive electrode sheet and A-side separator which are arranged in sequence are wound up.
[0042] In an optional embodiment, the winding tension fa of the A-side diaphragm is greater than the winding tension fb of the B-side diaphragm;
[0043] Preferably, the winding tension of the A-side diaphragm and the B-side diaphragm satisfies:
[0044] fb=k4×70.986×e 0.0027fa ;
[0045] Among them, the value of k4 is 0.8-1.3, and the value of fa is 90gf-800gf.
[0046] The present invention has the following beneficial effects: the present invention defines the A-side diaphragm and the B-side diaphragm, and adjusts the parameters of the A-side diaphragm, the B-side diaphragm and the negative electrode sheet to meet a specific relationship, and utilizes the unique properties of the A-side diaphragm and the B-side diaphragm to improve the battery interface, wherein the B-side diaphragm is a single-sided adhesive layer that can undergo a large deformation under the action of high temperature and pressure, thereby on the one hand releasing the expansion of the space-consuming negative electrode sheet; on the other hand, utilizing the large gap between the adhesive layers to discharge the gas generated during formation. The cylindrical battery that meets the special relationship defined by the present invention can better optimize the interface stress release and the emission of the gas produced by formation of the wound cylindrical battery, which is beneficial to improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0048] Figure 1 Schematic diagram of cylindrical battery winding;
[0049] Figure 2 It is a schematic diagram of the B-side diaphragm structure;
[0050] Figure 3 This is a schematic diagram of the basic unit of a cylindrical battery roll core;
[0051] Figure 4 It is the battery white spot interface;
[0052] Figure 5 To improve the rear battery interface. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0054] The present invention provides a cylindrical battery, such as Figure 1 As shown, it is formed by winding the negative electrode sheet, B-side separator, positive electrode sheet and A-side separator arranged in sequence, and after the winding is completed, the central axis is removed to obtain a cylindrical battery.
[0055] In the embodiment of the present invention, the battery interface is improved by using a specific type of A-side separator and B-side separator at the design end, and utilizing the unique properties of the A-side separator and the B-side separator. Specifically, the A-side separator is a base film, and the B-side separator includes a base film and a coating layer coated on the base film. The parameters of the A-side separator, the B-side separator and the negative electrode sheet satisfy the following relationship:
[0056] h3=k1×ha×ρ / 2, where k1=0.9-1.1;
[0057] σb=k2×σa×(1-λ)×(1-Ψ), where k2 is 1.3-1.6;
[0058] h2+h3=h1×k3, the value of k3 is 90%-110%;
[0059] In the formula, h1 represents the thickness of the A-side diaphragm, in μm;
[0060] h2 represents the thickness of the base film of the B-side diaphragm, in μm;
[0061] h3 represents the thickness of the coating layer, in μm;
[0062] ha represents the thickness of the negative electrode at 0% SOC, in μm;
[0063] ρ represents the full-charge expansion rate of the negative electrode, in %;
[0064] σb represents the porosity of the base film of the B-side diaphragm, in %;
[0065] σa represents the porosity of the A-side diaphragm, in %;
[0066] λ represents the ratio of the coating area of the coating layer to the base film area, in %;
[0067] ψ represents the swelling of the coating layer, in %.
[0068] Specifically, the value of k1 can be 0.9, 1.0, 1.1, etc., the value of k2 can be 1.3, 1.4, 1.5, 1.6, etc., and the value of k3 can be 90%, 95%, 100%, 105%, 110%, etc.
[0069] It should be noted that the inventor creatively made the parameters of the A-side separator, the B-side separator and the negative electrode sheet satisfy a specific relationship, which can reduce the deformation stress during the later cycle expansion of the battery, thereby increasing the life of the battery. The above design is used to optimize the interface stress release and the emission of the formed gas of the wound cylindrical battery.
[0070] The A-side separator is a base membrane, and the porosity is σa, and the value of σa is 30%-60%, such as 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc. The thickness of the A-side separator is h1, and the value of h1 is 5μm-30μm, such as 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, etc. The material of the A-side separator can be polyethylene (PE), but is not limited thereto.
[0071] like Figure 2 As shown, the B-side diaphragm includes a base film and a coating layer coated on the base film, the porosity of the base film is σb, and the value range of σb is 30%-60%, such as 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc. The thickness of the base film is h2, and the value range of thickness h2 is 6μm-30μm, such as 6μm, 10μm, 15μm, 20μm, 25μm, 30μm, etc. The material of the base film is not limited, as long as it meets the above porosity and thickness, such as polypropylene (PP).
[0072] The swelling of the coating layer on the B-side diaphragm is ψ, and the value of ψ can be 2%-10%, such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. The swelling of the coating layer can be detected by conventional test methods, and the specific method is referred to GB / T2951. The thickness of the coating layer can be h3, and the thickness of the coating layer refers to the total thickness of the diaphragm minus the thickness of the base film. The specific thickness can be calculated according to the subsequent relationship.
[0073] Furthermore, the material of the coating layer is selected from at least one of polyvinylidene fluoride, epoxy resin, polyurethane, acrylate and silane, and the material of the coating layer can be any one or more of the above. The coating layer is formed by a dot coating process and is coated on one side of the base film. The single-sided adhesive layer can undergo a large deformation under the action of high temperature and pressure, thereby releasing the expansion of the space-consuming negative electrode sheet on the one hand, and using the larger gaps between the adhesive layers to discharge the gas generated during the formation on the other hand. The ratio of the coating area of the coating layer to the base film area is λ, and the value of λ can be 10%-40%, such as 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc.
[0074] The full-charge expansion rate of the negative electrode sheet is ρ, which can be 0%-30%, such as 0%, 5%, 10%, 15%, 20%, 25%, 30%, etc. The thickness of the negative electrode active layer of the negative electrode sheet at 0% SOC is ha, which can be 50μm-200μm, such as 50μm, 80μm, 100μm, 130μm, 150μm, 180μm, 200μm, etc. Specifically, the negative electrode sheet can be a commercially available negative electrode sheet, and its product parameters are marked with the full-charge expansion rate ρ and the specific values of the negative electrode active layer thickness ha at 0% SOC.
[0075] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active coating attached to both sides of the negative electrode current collector, the active material in the negative electrode active coating is selected from at least one of graphite, silicon-based negative electrode and lithium titanate, and the negative electrode active material can be any one or more of the above. The negative electrode current collector can be copper foil, but is not limited thereto. Specifically, the negative electrode sheet can be a commercially available product, and commercially available products that meet the above conditions are suitable for use as the negative electrode sheet of a cylindrical battery.
[0076] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active coating attached to both sides of the positive electrode current collector, the active material in the positive electrode active coating is selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide and lithium iron phosphate, and the positive electrode active material can be any one or more of the above. The positive electrode current collector can be aluminum foil, but is not limited thereto. Specifically, the positive electrode sheet can be a commercially available product, and commercially available products that meet the above conditions are suitable for use as the positive electrode sheet of a cylindrical battery.
[0077] In addition, the cylindrical battery provided in the embodiment of the present invention also includes an electrolyte and a structural part. The specific composition of the electrolyte is not limited, and a common electrolyte for lithium batteries can be used. It can also include a shell, which can be a steel shell or an aluminum shell.
[0078] The embodiment of the present invention further provides a method for preparing a cylindrical battery, comprising: when providing an A-side separator, a B-side separator and a negative electrode sheet, making each parameter satisfy the following relationship:
[0079] h3=k1×ha×ρ / 2, where k1=0.9-1.1;
[0080] σb=k2×σa×(1-λ)×(1-Ψ), where k2 is 1.3-1.6;
[0081] h2+h3=h1×k3, the value of k3 is 90%-110%;
[0082] The negative electrode sheet, B-side separator, positive electrode sheet and A-side separator which are arranged in sequence are wound up.
[0083] It should be noted that the specific meanings and value ranges of the above parameters can be found in the above description and will not be repeated here.
[0084] like Figure 1 and Figure 3 As shown, it is defined that both the positive electrode sheet and the negative electrode sheet have an A side and a B side, where the A side is the side close to the center of the circle and the B side is the side away from the center of the circle; the winding order is that the A-side separator faces the A side of the negative electrode sheet and the B side of the positive electrode sheet; the B-side separator has a coating layer on one side facing the B side of the negative electrode sheet, and the other side facing the A side of the positive electrode sheet.
[0085] In some embodiments, the winding tension fa of the A-side diaphragm is greater than the winding tension fb of the B-side diaphragm. The inventors found that the reason why white spots appear in the cylindrical battery prepared by the winding process is related to the winding tension of the A-side diaphragm and the B-side diaphragm. By adjusting the winding tension fa of the A-side diaphragm to be greater than the winding tension fb of the B-side diaphragm, the appearance of white spots on the cylindrical battery obtained by winding can be better avoided.
[0086] In a preferred embodiment, the winding tension of the A-side diaphragm and the B-side diaphragm satisfies:
[0087] fb=k4×70.986×e 0.0027fa ;
[0088] Among them, the value of k4 is 0.8-1.3 (such as 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, etc.), and the value of fa is 90gf-800gf (such as 90gf, 100gf, 200gf, 300gf, 400gf, 500gf, 600gf, 700gf, 800gf, etc.). By precisely controlling the winding tension of the A-side separator and the B-side separator, the effect of the cylindrical battery interface is further improved to avoid the appearance of white spot interface.
[0089] It should be noted that by adjusting the tension of the A and B side separators during winding, a certain gap is formed between the A side separator and the negative electrode sheet to provide a channel for the gas generated by the formation. The B side separator with a small winding tension will reduce the deformation stress in the later cycle expansion. The above design is used to optimize the interfacial stress release of the wound cylindrical battery and the emission of the gas generated by the formation. The tension and the selection of foil are adjusted by using the changes in curvature and core diameter to achieve a long battery life cycle.
[0090] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0091] Example 1
[0092] This embodiment provides a method for preparing a cylindrical battery, the steps are as follows:
[0093] (1) Provide positive electrode sheets, negative electrode sheets, and separators
[0094] The positive electrode sheet is a commercially available 46140 type positive electrode sheet with double-sided active coating, the active material is LFP, and the current collector is an aluminum foil with a thickness of 13 μm.
[0095] The negative electrode sheet is a commercially available 46140 model negative electrode sheet, the active material is graphite, has a double-sided active coating, and the current collector is a copper foil with a thickness of 6 μm. The thickness of the negative electrode sheet at 0% SOC state is 120 μm, and the full-charge expansion rate ρ of the negative electrode sheet is 18%.
[0096] The material of the A-side separator is a commercially available PE film with a thickness h1 of 15 μm and a porosity σa of 38%.
[0097] Preparation process of B-side diaphragm: a coating layer is formed on the PP base film by a spot coating process, the thickness h2 of the PP base film is 6.78μm, and the porosity σb is 33.54%; the material of the coating layer is polyvinylidene fluoride, the coating layer thickness h3 is 9.72μm, the ratio of the coating area of the coating layer to the base film area λ is 30%, and the swelling ψ of the coating layer is 3%.
[0098] After calculation, each parameter satisfies the following relationship:
[0099] Relationship 1: h3 = k1 × ha × ρ / 2, where k1 = 0.9;
[0100] Relation 2: σb = k2 × σa × (1-λ) × (1-Ψ), where k2 = 1.3;
[0101] Relationship 3: h2+h3=h1×k3, k3=1.1;
[0102] The parameters of the A-side separator, the B-side separator and the negative electrode sheet provided in Example 1 meet the requirements of the three relationship equations.
[0103] (2) Roll Rao
[0104] like Figure 1 and Figure 3 As shown, the negative electrode sheet, the B-side separator, the positive electrode sheet and the A-side separator are wound in sequence. It is defined that both the positive electrode sheet and the negative electrode sheet have an A-side and a B-side, the A-side is the side close to the center of the circle, and the B-side is the side away from the center of the circle; the winding order is that the A-side separator faces the A-side of the negative electrode sheet and the B-side of the positive electrode sheet; the B-side separator with a coating layer faces the B-side of the negative electrode sheet, and the other side faces the A-side of the positive electrode sheet.
[0105] During the winding process, the winding tension fa of the A-side diaphragm is controlled to be greater than the winding tension fb of the B-side diaphragm. The winding tensions of the A-side diaphragm and the B-side diaphragm satisfy:
[0106] Relationship 4: fb = k4 × 70.986 × e 0.0027fa ;
[0107] Among them, k4=1, the value of fa is 100gf, and the value of fb is 92.9891gf.
[0108] The diameter of the winding core used during winding is 45mm, and the center axis is removed after the thickness reaches the requirement.
[0109] (3) Liquid injection and formation
[0110] The intermediate product obtained in step (2) is packaged to form a steel shell, and then liquid is injected and formed.
[0111] Among them, the injected electrolyte composition is as follows: 13% LiPF6, 30% EC, 20% EMC, 50% DMC, 2% VC, 1.5DTD, and 3% FEC.
[0112] Embodiment 2-4
[0113] The only difference from Example 1 is that the values of the parameters in step (1) are different, see Table 1 for details.
[0114] Example 5
[0115] The only difference from Example 1 is that during winding in step (2), the winding tension fa of the A-side diaphragm is controlled to be greater than the winding tension fb of the B-side diaphragm, but the winding tensions of the A-side diaphragm and the B-side diaphragm do not satisfy:
[0116] fb=k4×70.986×e 0.0027fa ;
[0117] Among them, the value of fa is 500gf and the value of fb is 328.588gf.
[0118] Example 6
[0119] The only difference from Example 1 is that during winding in step (2), the winding tension fa of the A-side diaphragm is controlled to be smaller than the winding tension fb of the B-side diaphragm, wherein the value of fa is 500 gf and the value of fb is 800 gf.
[0120] Table 1 Parameter values of Examples 1-6
[0121]
[0122] Comparative Examples 1-4
[0123] The only difference from Example 1 is that the values of the parameters in step (1) are different, see Table 2 for details.
[0124] Table 2 Parameter values of comparative examples 1-4
[0125]
[0126] Test Example 1
[0127] The performance of the cylindrical batteries prepared in the examples and comparative examples was tested, and the results are shown in Table 3. The specific steps of testing whether there are white spots are as follows: disassembling the 100% SOC battery cell after formation and observing the interface morphology.
[0128] Table 3 Performance of cylindrical batteries prepared in Examples and Comparative Examples
[0129]
[0130] "Diving" in the table means battery failure.
[0131] It can be seen from Table 3 that the cycle performance of the cylindrical battery prepared in the embodiment of the present invention is significantly better than that of the comparative example.
[0132] The white spot detection results of the cylindrical battery prepared in Comparative Example 1 are as follows: Figure 4 As shown, it can be seen that white spot interface appears on the battery surface.
[0133] The white spot detection results of the cylindrical battery prepared in Test Example 1 are as follows: Figure 5 As shown in Figure 2, it can be seen that no white spot interface appears on the battery surface.
[0134] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A cylindrical battery, characterized in that: It is formed by winding a negative electrode sheet, a B-side separator, a positive electrode sheet and an A-side separator which are arranged in sequence; Wherein, the A-side diaphragm is a base film, and the B-side diaphragm includes a base film and a coating layer coated on the base film; The parameters of the A-side separator, the B-side separator and the negative electrode sheet satisfy the following relationship: h3=k1×ha×ρ / 2, where k1=0.9-1.1; σb=k2×σa×(1-λ)×(1-Ψ), where k2 is 1.3-1.6; h2+h3=h1×k3, the value of k3 is 90%-110%; Wherein, h1 represents the thickness of the A-side diaphragm, in μm; h2 represents the thickness of the base film of the B-side diaphragm, in μm; h3 represents the thickness of the coating layer, in μm; ha represents the thickness of the negative electrode sheet at 0% SOC, in μm; ρ represents the full-charge expansion rate of the negative electrode, in %; σb represents the porosity of the base film of the B-side diaphragm, in %; σa represents the porosity of the A-side diaphragm, in %; λ represents the ratio of the coating area of the coating layer to the base film area, in %; ψ represents the swelling of the coating layer, in %.
2. The cylindrical battery according to claim 1, characterized in that: The material of the A-side diaphragm is polyethylene.
3. The cylindrical battery according to claim 1 or 2, characterized in that: The porosity σa of the A-side diaphragm is 30%-60%; And / or, the thickness h1 of the A-side diaphragm is 5 μm-30 μm.
4. The cylindrical battery according to claim 1, characterized in that: The base film of the B-side diaphragm is made of polypropylene; And / or, the porosity σb of the base film is in the range of 30%-60%, and the thickness h2 is in the range of 6 μm-30 μm; And / or, the coating layer is made of at least one material selected from polyvinylidene fluoride, epoxy resin, polyurethane, acrylate and silane.
5. The cylindrical battery according to claim 1, characterized in that: The swelling value of the coating layer is 2%-10%; And / or, the ratio λ of the coating area of the coating layer to the base film area is 10%-40%; And / or, the coating layer is formed by a dot coating process and is coated on one side of the base film.
6. The cylindrical battery according to claim 1, characterized in that: The full charge expansion rate ρ of the negative electrode sheet is 0%-30%; And / or, the thickness ha of the negative electrode active layer of the negative electrode sheet at 0% SOC state is 50 μm-200 μm.
7. The cylindrical battery according to claim 1, characterized in that: It is defined that both the positive electrode sheet and the negative electrode sheet have an A surface and a B surface, wherein the A surface is the surface close to the center of the circle, and the B surface is the surface away from the center of the circle; The winding order is that the A-side separator faces the A-side of the negative electrode sheet and the B-side of the positive electrode sheet; the B-side separator has one side with a coating layer facing the B-side of the negative electrode sheet and the other side facing the A-side of the positive electrode sheet.
8. The cylindrical battery according to claim 1, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating attached to both sides of the negative electrode current collector, wherein the active material in the negative electrode active coating is selected from at least one of graphite, silicon-based negative electrode and lithium titanate; And / or, the positive electrode sheet includes a positive electrode current collector and a positive electrode active coating attached to both sides of the positive electrode current collector, and the active material in the positive electrode active coating is selected from at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide and lithium iron phosphate.
9. A method for preparing a cylindrical battery according to any one of claims 1 to 8, characterized in that: include: When providing the A-side separator, the B-side separator and the negative electrode sheet, the parameters are made to satisfy the following relationship: h3=k1×ha×ρ / 2, where k1=0.9-1.1; σb=k2×σa×(1-λ)×(1-Ψ), where k2 is 1.3-1.6; h2+h3=h1×k3, the value of k3 is 90%-110%; The negative electrode sheet, B-side separator, positive electrode sheet and A-side separator which are arranged in sequence are wound up.
10. The preparation method according to claim 9, characterized in that: The winding tension fa of the A-side diaphragm is greater than the winding tension fb of the B-side diaphragm; Preferably, the winding tension of the A-side diaphragm and the B-side diaphragm satisfies: fb=k4×70.986×e 0.0027fa ; Among them, the value of k4 is 0.8-1.3, and the value of fa is 90gf-800gf.